Hubungan Konflik Peran Ganda dan Stres Kerja dengan Psychological Well Being Perawat di RSUD Dr. R. Goeteng Taroenadibrata Purbalingga - Dinda Artanti Septiana (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The psychological well-being felt by nurses is important because it has an optimal influence on whether nurses work or not. Psychological well-being in nurses can be caused by many aspects, including problems with multiple roles and work stress. In this way, the aim of the research is to understand the relationship between dual roles, work stress, and the psychological well-being of nurses at RSUD, Dr. R. Goeteng Taroenadibrata Purbalingga. The method taken is quantitative with a descriptive correlational design and cross-sectional design, as well as a sampling technique with total sampling. Data analysis utilized the Spearman Rank test. The output of the research was from 70 nurses at RSUD Dr. R. Goeteng Taroenadibrata Purbalingga. The majority experienced dual role conflict, which was at a moderate level; there were 32 nurses (45.7%), work stress was in the moderate category, 40 people (57.1%), and psychological well-being was in the medium category, 43 nurses. (61.4%). The results of the data analysis show that there is an influential correlation between the problem of dual roles and the psychological well-being of nurses (p-value = 0.000 and rho = 0.885). Apart from that, there is also an influential correlation between work stress and the psychological well-being of nurses (p-value = 0.000 and rho value = 0.775).The psychological well-being felt by nurses is important because it has an optimal influence on whether nurses work or not. Psychological well-being in nurses can be caused by many aspects, including problems with multiple roles and work stress. In this way, the aim of the research is to understand the relationship between dual roles, work stress, and the psychological well-being of nurses at RSUD, Dr. R. Goeteng Taroenadibrata Purbalingga. The method taken is quantitative with a descriptive correlational design and cross-sectional design, as well as a sampling technique with total sampling. Data analysis utilized the Spearman Rank test. The output of the research was from 70 nurses at RSUD Dr. R. Goeteng Taroenadibrata Purbalingga. The majority experienced dual role conflict, which was at a moderate level; there were 32 nurses (45.7%), work stress was in the moderate category, 40 people (57.1%), and psychological well-being was in the medium category, 43 nurses. (61.4%). The results of the data analysis show that there is an influential correlation between the problem of dual roles and the psychological well-being of nurses (p-value = 0.000 and rho = 0.885). Apart from that, there is also an influential correlation between work stress and the psychological well-being of nurses (p-value = 0.000 and rho value = 0.775).